Safety Evaluation Of Sjenica Cheese With Regard To Coagulase-Positive Staphylococci And Antibiotic Resistance Of Lactic Acid Bacteria And Staphylococci - Bulajić Snežana (Sciendo, 2015)
Sjenica cheese is an artisanal cheese stored in brine, traditionally produced from raw sheep’s milk in the southern part of Serbia - Sjenica Pester plateau.